Sosialisasi Penerapan Biosecurity Dalam Budidaya Udang Vaname (Litopenaeus Vannamei) di Desa Kuranji Dalang, Lombok Barat - Lestari, Dewi Putri; Lumbessy, Salnida Yuniarti; Abidin, Zaenal; Diamahesa, Wastu Ayu; Rahmadani, Thoy Batun Citra (Universitas Mataram, 2024)
The application of the biosecurity system as an effort to prevent failures in aquaculture activities, one of which is vaname shrimp farming. Because in aquaculture activities it is known that the water sources used come from natural water sources. Like in the Kuranji area where the source of sea water comes from Kuranji Beach. So that the water area qualifies as an open water area (Open System) and there is a greater possibility of microbiological and chemical contaminants being carried into the aquaculture system through water. Therefore, it is necessary to socialize the introduction of biosecurity systems by making water filters as an effort to prevent microbiology that can interfere with shrimp farming activities.